Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.435
|View full text |Cite
|
Sign up to set email alerts
|

Event Detection: Gate Diversity and Syntactic Importance Scores for Graph Convolution Neural Networks

Abstract: Recent studies on event detection (ED) have shown that the syntactic dependency graph can be employed in graph convolution neural networks (GCN) to achieve state-of-the-art performance. However, the computation of the hidden vectors in such graph-based models is agnostic to the trigger candidate words, potentially leaving irrelevant information for the trigger candidate for event prediction. In addition, the current models for ED fail to exploit the overall contextual importance scores of the words, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Traditional EE methods (Ji and Grishman, 2008;Gupta and Ji, 2009;Li et al, 2013) rely on manually-crafted features to extract events. In recent years, the neural models become mainstream, which automatically learn effective features with neural networks, including convolutional neural networks (Nguyen and Grishman, 2015;Chen et al, 2015), recurrent neural networks (Nguyen et al, 2016), graph convolutional networks (Nguyen and Grishman, 2018;Lai et al, 2020). With the recent successes of BERT (Devlin et al, 2019), PLMs have also been used for EE (Wang et al, 2019a,b;Yang et al, 2019;Wadden et al, 2019;Tong et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional EE methods (Ji and Grishman, 2008;Gupta and Ji, 2009;Li et al, 2013) rely on manually-crafted features to extract events. In recent years, the neural models become mainstream, which automatically learn effective features with neural networks, including convolutional neural networks (Nguyen and Grishman, 2015;Chen et al, 2015), recurrent neural networks (Nguyen et al, 2016), graph convolutional networks (Nguyen and Grishman, 2018;Lai et al, 2020). With the recent successes of BERT (Devlin et al, 2019), PLMs have also been used for EE (Wang et al, 2019a,b;Yang et al, 2019;Wadden et al, 2019;Tong et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has shown that event-related structures are helpful in extracting new events (Lai et al, 2020) as well as discovering and generalizing to new event schemata (Huang et al, 2016(Huang et al, , 2018Huang and Ji, 2020). Hence we conduct event structure pre-training on a GNN as graph encoder to learn transferable event-related structure representations with recent advances in graph contrastive pre-training (Qiu et al, 2020;You et al, 2020;.…”
Section: Event Structure Pre-trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…ED has been studied extensively in the last decade, featuring feature-based models (Ahn, 2006;Ji and Grishman, 2008;Li et al, 2013Li et al, , 2015, deep learning models (Chen et al, 2015; 2016b,a; Nguyen and Grishman, 2016; Liu et al, 2018;Yan et al, 2019;Ngo et al, 2020;Lai et al, 2020b), and few/zero-shot learning models (Huang et al, 2018;Lai and Nguyen, 2019;Lai et al, 2020a). The rapid development of such models has been facilitated by the availability of the ED datasets in different domains, including the general domain with the popular ACE and TAC KBP datasets (Walker et al, 2006;Mitamura et al, 2015Mitamura et al, , 2016, the biomedical domain (Kim et al, 2009(Kim et al, , 2011, literature (Sims et al, 2019), cybersecurity (Satyapanich et al, 2020;Man Duc Trong et al, 2020), and the open domain (Araki and Mitamura, 2018;Liu et al, 2019b).…”
Section: Related Workmentioning
confidence: 99%
“…Event triggers represent the most important words (usually single verbs or nominalizations) in the sentences that evoke the events. The current state-of-the-art methods for ED feature the deep learning models where many new network architectures are introduced in the last couple of years Chen et al, 2015;Liu et al, , 2019aLai et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%